Effectiveness of carboxytherapy in the treatment of cellulite in healthy women: a pilot study - Pianez LR; Custódio FS; Guidi RM; de Freitas JN; Sant'Ana E (Dove Medical Press, 2016)
Luana Ramalho Pianez,1 Fernanda Silva Custódio,1 Renata Michelini Guidi,1-4 Jauru Nunes de Freitas,5-7 Estela Sant’Ana8-10 1Ibramed Center for Education and Advanced Training (CEFAI), Amparo, 2Santa Casa de Misericórdia Hospital, Porto Alegre, 3University of Campinas, Campinas, 4Ibramed Research and Development Department, Amparo, São Paulo, Brazil; 5Universitá Tor Vergata, Rome, Italy; 6Centro de Medicina Pesquisa e Ensino (CEMEPE), Belo Horizonte, 7Advanced Dermatology Studies Group (GDA), Rio de Janeiro, 8Federal University of São Carlos (UFSCAR), 9University of São Paulo (USP), São Carlos, 10Indústria Brasileira de Equipamentos Médicos (IBRAMED), Amparo, São Paulo, Brazil Background: Carbon dioxide therapy, better known as carboxytherapy, relates to percutaneous infusion of medical carbon dioxide with therapeutic approaches, and its use in the treatment of localized fat has demonstrated good results. Gynoid lipodystrophy, also known as cellulite, affects 80%–90% of women after puberty, especially in the buttocks and thighs. Its etiology is complex and involves multifactorial aspects. Its treatment and evaluation require the use of new technologies (more effective and low-cost approaches). The objective was to investigate the effectiveness of carboxytherapy in the treatment of cellulite in the areas of buttocks and posterior thigh.Patients and methods: Ten women, 29±6.1 years, were selected and all of them received eight treatment sessions, with an interval of 7 days between sessions. Standardized digital photographs were used to assess the severity of cellulite, and panoramic images were collected by ultrasound diagnosis. The evaluations were performed before the first treatment (baseline) and 7 days after the last treatment session of carboxytherapy.Results: After the treatment, there was a significant reduction (P=0.0025) of the cellulite from degree III to degree II, and this improvement had correlation with the improvement in the organization of the fibrous lines and the disposal of adipose tissue lines of the treated regions observed through the panoramic ultrasound images diagnosis.Conclusion: Carboxytherapy is an effective technique of treatment of cellulite in the buttocks region and posterior thighs of healthy women. Keywords: carbon dioxide, cellulite, localized fat, gynoid lipodystrophy, skin, panoramic ultrasound